Diseño de un reactor de pirólisis rápida en la producción de combustible a base de plástico PET para la implementación en los laboratorios de la Universidad de América. (2022)
In the present work, we seek to carry out a detailed design of a fast pyrolysis reactor for plastic waste for the production of fuel, which contributes to the generation of eco-efficient technological alternatives. To comply with this project, the design parameters of the pyrolysis reactor will be determined, such as thermal conditions, properties of the raw material, processing capacity, in order to obtain a basis for the investigation. Even each of the configurations and types of reactors to carry out the aforementioned process that are available in the literature will be analyzed.